2016
DOI: 10.1103/physreva.93.012506
|View full text |Cite
|
Sign up to set email alerts
|

Positronium decay fromn=2states in electric and magnetic fields

Abstract: We report measurements and the results of calculations demonstrating that the annihilation dynamics of positronium (Ps) atoms can be controlled by Stark and Zeeman mixing of optically excited states. In the experiments a trap-based pulsed positron beam was employed to generate a dilute Ps gas with a density of ∼10 7 cm −3 using a porous silica target. These atoms were excited via 1 3 S 1 → 2 3 P J transitions in parallel electric and magnetic fields using a nanosecond pulsed dye laser, and Ps annihilation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 100 publications
1
40
0
Order By: Relevance
“…These data are included explicitly in the simulation so that the electric field experienced by different 053417-6 atoms as a function of time can be represented. Other than scaling the laser off f values to account for the prompt Ps annihilation peak, the Monte Carlo simulations contain no free parameters and are expected to be both qualitatively and quantitatively comparable to the measured data [32].…”
Section: Simulationsmentioning
confidence: 97%
“…These data are included explicitly in the simulation so that the electric field experienced by different 053417-6 atoms as a function of time can be represented. Other than scaling the laser off f values to account for the prompt Ps annihilation peak, the Monte Carlo simulations contain no free parameters and are expected to be both qualitatively and quantitatively comparable to the measured data [32].…”
Section: Simulationsmentioning
confidence: 97%
“…Having shown that existing measurements are too imprecise resolve this splitting, one can ask about the future prospects. Upcoming experiments at University College London plan to remeasure the n = 2 fine-structure with a reduced uncertainty yielding ∆ 2,P ∼ 100 kHz [36][37][38]. A measurement of ∆ 2,P would require only a factor of two improvement.…”
mentioning
confidence: 99%
“…For excitation to states that rapidly fluoresce (e.g., 2P) the overall lifetime is thereby reduced. The effect had on SS-PALS spectra is similar to REMPI, albeit weaker because of competition with decay to the triplet ground state [19].…”
Section: Rempimentioning
confidence: 81%